Functionally-morphological kidneys condition in patients with rheumatoid arthritis - M. I. Kalyuzhina; Ye. O. Bukharova; A. Yu. Shatuta; Ye. V. Kalyuzhina; L. I. Zibnitskaya; L. V. Yeliseyeva (Бюллетень сибирской медицины)
The aim of the investigation was to study the functional-morphological state of kidney in patients with rheumatoid arthritis (RА). Examination was performed on 75 patients with RA and 25 healthy subjects. In addition to complete clinical and instrumental examination accepted in specialised clinic, biopsy of kidney was conducted. At 62 patients changes in an urinary deposit are taped. According to 25 nephrobiopsies in 12 cases took place mesangioproliferative variant of a chronic glomerulonephritis, the amyloidosis was detected at 5 patients, in 8 cases - vascular changes, the weak and moderate phenomena of a productive vasculitis of arterioles, the capillaries, accompanied by a focal perivascular sclerosis. Nephroprotective effect of basic therapy of RА was found.